A Review on Various IoT based Security and Automation System - J, Maya; N, Megha; R, Meghana; V, Nisarga (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
IoT based home security is the concept of monitoring and controlling household appliances using the internet as the medium irrespective of the location of the owner of the house. This is a review paper on three different ways of implementing Iot based Home security and Home automation. All the system discussed here aims at sensing the changes in the house and sending an alert message to the owner through different ways like SMS, voice call or facebook status, so that the owner can take further actions accordingly to safe guard his/her house.